Manajemen Sumberdaya dalam Strategi Pengelolaan Limbah Medis Rumah Sakit Islam Kota Malang di Masa Pandemi Covid-19 - Nastiti, Bahagia (Jurnal Ilmiah Administrasi Publik, 2022)
Resource management in the management of medical waste is a cruicial issue in the midst of Covid-19 pandemic. This study aims to analyze the management of hazardous and toxic waste management resources at the Islamic Hospital (RSI) Malang City by adopting descriptive research through a qualitative approach. Findings of this study found a discrepancy between the Standard Operating Procedures (SOP) and the realization of activities in the field, especially when there was a surge in Covid-19 patients due to the rapid increase in waste generation. This leads the delays in transportation which results in the accumulation of waste. Delays in transporting waste has potential to cause environmental pollution. Hence, it is necesarry to conduct a review of SPO to deal with the threat of Covid-19 spike in the future.